Difference in Hip Prosthesis Femoral Offset Affects Hip Abductor Strength and Gait Characteristics During Obstacle Crossing - Chamnongkich S. (2017)
The purpose of this article is to determine if individuals with high rather than low femoral offset of a total hip arthroplasty achieve improved hip abductor muscle strength and thus improved their ability to step over an obstacle safely. These outcomes will help surgeons decide whether increasing the femoral offset helps a patient's physical function. © 2012 Elsevier Inc.